ASSESMEN PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI PONDOK PESANTREN AL-MUNAWIR AL-FATHIMIYAH KRAPYAK - Hasna, Salsabila Nur (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to understand the social-emotional development of early childhood living in the pesantren environment, especially in the Al-Munawir Krapyak Islamic Boarding School. Using a qualitative descriptive approach and purposive random sampling techniques, this study highlights how social interactions that occur between students, ustadz, and daily routines such as sharing, queuing, and resolving conflicts contribute significantly to the formation of children’s social and emotional character. The results of the study show that a structured pesantren environment with Islamic values plays a role in fostering empathy, independence, responsibility, and the ability to manage emotions in children. Within the framework of Bronfenbrenner’s Theory of Ecology, these developments are influenced not only by the immediate environment (microsystem), but also by inter-environmental relationships (mesosystems), indirect influences (exosystems), cultural values (macrosystems), and the dynamics of time changes (chronosystems). A pesantren culture that upholds values such as discipline, simplicity, and togetherness is a key factor in shaping children’s personalities holistically. Thus, the assessment of social-emotional development is an important instrument in designing appropriate and contextual coaching strategies for early childhood in the pesantren environment.